61 Abbreviations in medical practice- time saving or time consuming?. (31st October 2017) - McClelland, K; Sweeney, M; Moore, I
Abstract : Aims: To highlight the strengths, weaknesses and potential patient safety issues regarding the abbreviation use in medical admissions in Belfast City Hospital. To inform and educate all staff regarding the safe and efficient use of medical abbreviations. Methods: To determine the extent of the problem we carried out a survey of staff members regarding the use of abbreviations. We then retrospectively reviewed 30 medical admission booklets to identify the type and number of abbreviations used. We separated the abbreviations into four categories; 1) Diagnosis, 2) Symptoms, 3) Examination findings, and 4) Management. We then selected five abbreviations from each of the four categories and created a questionnaire asking members of the MDT to describe their meaning. The questionnaire was distributed to 72 healthcare professionals. Results: The current standard based on our questionnaire results suggested that 79% of our respondents had encountered an abbreviation in the preceding 3 months that they didn't understand. Due to these results, we formalised an education session to create awareness of current Belfast Trust Guidelines and invited all medical staff. This session also highlighted the concerns as demonstrated by our findings and highlighted the deviations from Trust Guidelines. Conclusions: This project, though not yet complete, has highlighted the difficulties with the use of abbreviations in clinical practice. Whilst they can be efficient and time-saving when used inappropriately they represent a patient safety issue. Our next goal is to address the list of currently accepted abbreviations which excludes many commonly used abbreviations. By updating guidelines and distributing them together with formal education sessions we seek to improve standards on abbreviation use. We appreciate that initiating culture change is a timely process but improving awareness and providing useful guidelines will be crucial to change and patient safety.